Effectiveness of Spironolactone for Acne Vulgaris - Wong Hendra Wijaya; Arini Astasari Widodo; Chearin Dea Sanfika (Jurnal MedScientiae, 2023)
Acne vulgaris is a skin disease that attacks pilosebaceous follicles which can be either inflammatory or non-inflammatory lesion. One of the important factors causing acne vulgaris is androgen hormone. One of the hormonal therapies that can be given for acne vulgaris is spironolactone which has a function as an antiandrogen. The purpose of writing this literature review is to determine the effectiveness, mode of action, indications, contraindications, and side effects of spironolactone in the treatment of acne vulgaris. The method in making this final project is Literature Review. Literature searches were obtained using electronic databases such as Google Scholar, PubMed, Proquest, International Journal of Women's Dermatology, and NCBI. The keywords used were spironolactone, hormonal therapy, acne vulgaris, effectiveness of spironolactone for acne vulgaris. There are 10 supporting journals based on the suitability of topics in the last 10 years. The results showed that the administration of spironolactone for acne vulgaris proved to be effective with an average dose of 50-100 mg/day which resulted in 70-90% clinical improvement and caused minimal side effects. Spironolactone has good effectiveness and tolerability for alternative therapy of acne vulgaris in adult women and for patients who do not respond well to conventional therapy.